Vocation of Human Care and Soft Skills in Nursing and Physiotherapy Students: A Cross-Sectional Study - Juan-Elicio Hernández-Xumet; Alfonso-Miguel García-Hernández; Jerónimo-Pedro Fernández-González; Cristo-Manuel Marrero-González (Nursing Reports)
Background: Empathy and assertiveness are two essential soft skills for health professionals such as nurses or physiotherapists. Both professions are characterised by their contribution to preserving and improving health and human care, and for their vocation of service. One of the achievements of the training is the voluntary, conscious, and individually inspired career choice. Objectives: This study aimed to evaluate the empathy, assertiveness, and care vocational levels among undergraduate students enrolled in Nursing and Physiotherapy Degree programmes and to investigate the relationship between these soft skills and the care vocation. Methods: A cross-sectional study of nursing and physiotherapy students was conducted in the 2023/2024 academic year. The Interpersonal Reactivity Index scales for empathy, the Rathus test for assertiveness, and the “Vocation of Service for Human Care” questionnaire were used as study tools. Finally, 226 nursing and physiotherapy students participated after providing informed consent, excluding those on national or international exchange programmes. Results: The empathy, assertiveness, and vocation of service for human care of the students was found to be acceptable. Significant differences were observed according to the gender variable or career among the students, with female students presenting better results in empathy subscales or vocation (p < 0.05). Students who were working or had clinical experience in other professions scored lower on the empathy personal distress subscale (p < 0.05). Conclusions: Both nursing and physiotherapy students demonstrate satisfactory levels of empathy, assertiveness, and vocation for human care. However, gender and previous work experience notably influence these scores. It would be beneficial to conduct long-term studies with educational interventions to train and develop empathy, assertiveness, and vocation for human care.